CORRELATION BETWEEN AUTONOMY AND FUTURE ORIENTATION FOR EMPLOYMENT AMONG GRADE XII STUDENTS OF VACATIONAL SCHOOL 7 BANDUNG - Asti Nopiani Nurfajar; Fridayanti Fridayanti; Elisa Kurniadewi (Psympathic : Jurnal Ilmiah Psikologi, 2012)
The aim of this research is studying the level of learning autonomy and future orientation students and correlation between those two variables. Quantitative design with correlational method was used. Sample are 62 students studying at vacational school majoring in textile chemistry SMKN7 Bandung. Result shows that there is positive correlation between learning autonomy and future orientation. High learning autonomy will make optimistic in future orientation while low learning autonomy result pesimistic future orientation.